Arrival time at a referral hospital and functional disability of people with stroke: a cohort study - Moraes, Mariana de Almeida; Jesus, Pedro Antônio de; Muniz, Ludimila Santos; Baccin, Camila Antunes; Barreto, Alexandra Bahia Mendonça; Sales, Rilary Silva; Pires, Cláudia Geovana da Silva; Teles, Carlos Antônio de Souza; Mussi, Fernanda Carneiro (São Paulo Medical Journal, 2023)
BACKGROUND: Stroke is a major cause of death and functional disability worldwide. Knowledge of the associated factors is essential for defining education, management, and healthcare strategies. OBJECTIVE: To analyze the association between arrival time at a neurology referral hospital (ATRH) and functional disability in patients with ischemic stroke 90 days after the event. DESIGN AND SETTING: Prospective cohort study conducted at a public institution of higher education in Brazil. METHODS: This study included 241 people aged ≥ 18 years who presented ischemic stroke. The exclusion criteria were death, inability to communicate without companions who could answer the research questions, and > 10 days since ictus. Disability was assessed using the Rankin score (mR). Variables for which associations showed a P value ≤ 0.20 in bivariate analysis were tested as modifiers between ATRH and disability. Significant interaction terms were used for multivariate analysis. Multivariate logistic regression analysis was performed with all variables, arriving at the complete model and adjusted beta measures. The confounding variables were included in the robust logistic regression model, and Akaike’s Information Criterion was adopted to choose the final model. The Poisson model assumes a statistical significance of 5% and risk correction. RESULTS: Most participants (56.0%) arrived at the hospital within 4.5 hours of symptom onset, and 51.7% presented with mRs of 3 to 5 after 90 days of ictus. In the multivariate model, ATRH ≥ 4.5 hours and females were associated with more significant disability. CONCLUSIONS: Arrival at the referral hospital 4.5 hours after the onset of symptoms or wake-up stroke was an independent predictor of a high degree of functional disability.